2023
DOI: 10.21203/rs.3.rs-2485721/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cervical cancer screening for PLWHIV; experiences from an innovative cervical screening and treatment program in Nigeria

Abstract: We evaluated cervical cancer program for women living with HIV (WLHIV) to determine program screening rate, primary case finder screening accuracy and treatment and post-treatment screening rate among screen-positive patients. Methods A one-year review of cervical cancer program data among WLHIV aged 15-49 years on HIV care across forty-one comprehensive ART sites supported by APIN (a PEPFAR implementing partner) in Nigeria was conducted from October 2020 to July 2021. Initial screening was done using visual i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…WLHIV having a much higher rate of 53.3% [18]. In Nigeria, a study using program data found a VIA positivity rate of 7.1% [19]. In another study assessing HPV testing for WLHIV, 46.5% in Burkina Faso and 43.8% in South Africa had a positive HPV test [20].…”
Section: Discussionmentioning
confidence: 98%
“…WLHIV having a much higher rate of 53.3% [18]. In Nigeria, a study using program data found a VIA positivity rate of 7.1% [19]. In another study assessing HPV testing for WLHIV, 46.5% in Burkina Faso and 43.8% in South Africa had a positive HPV test [20].…”
Section: Discussionmentioning
confidence: 98%